2017
DOI: 10.14814/phy2.13346
|View full text |Cite
|
Sign up to set email alerts
|

Pressure and stretch differentially affect proliferation of renal proximal tubular cells

Abstract: Renal obstruction is frequently found in adults and children. Mechanical stimuli, including pressure and stretch in the obstructed kidney, contribute to damage; animal models of obstruction are characterized by increased cellular proliferation. We were interested in the direct effects of pressure and stretch on renal tubular cell proliferation. Human HKC‐8 or rat NRK‐52E proximal tubule cells were subjected to either pressure [0, 60 or 90 mmHg] or static stretch [0 or 20%] for 24 or 48 h. Cell proliferation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…HKC cells are a group of cells that are mostly composed of normal human proximal tubular epithelial cells. HKC cells are widely used in pharmacological and toxicological experiments [31, 32]. GLUT9 is mainly distributed on the tubular apical membrane of the renal tubule.…”
Section: Discussionmentioning
confidence: 99%
“…HKC cells are a group of cells that are mostly composed of normal human proximal tubular epithelial cells. HKC cells are widely used in pharmacological and toxicological experiments [31, 32]. GLUT9 is mainly distributed on the tubular apical membrane of the renal tubule.…”
Section: Discussionmentioning
confidence: 99%
“…A significant increase in the number of apoptotic and proliferative tubular cells in inducible-NO synthase gene knockout mice, following unilateral obstructive nephropathy, was reportedly an indicative of the anti-apoptotic properties of NO, as demonstrated by Miyajima et al 27 Even though NO has complex effects on renal oxidative status, it exerts important anti-apoptotic protective effects in UUO. 28 Felsen et al 29 subjected cultured tubular epithelial cells to mechanical stretch as, an in vitro replication of UUO-induced tubular cellular stress to study the role of NO in apoptosis during UUO.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-dimensional (2D) pressure loading system was designed and manufactured by our research group, and the protocol can be found in our previous papers [14,29,30]. The Flexcell-5000 Compression System (Flexcell International Corp, Burlington, NC, US) was used to exert pressure on the 3D cultured cells.…”
Section: Pressure Loadingmentioning
confidence: 99%